Plan estratégico para la empresa Prometal de la ciudad de Loja - Córdova Iñiguez, Fabián Andrés (2017)
his thesis, entitled STRATEGIC PLAN FOR THE PROMETAL ENTERPRISE OF THE CITY OF LOJA, has as general objective to develop a Strategic Plan for the company PROMETAL, which allows to determine the commercial objectives to be achieved by detailing strategies and actions that will be carried out for To achieve them in a year, it is very reasonable to try to maximize profits and reduce expenses, so it is necessary to improve planning and organization within the company, with the sole purpose of presenting the owner a tool that facilitates the control And be of great help for the decision making and a proper administrative direction of the same In the first place a theoretical support was made that allowed to strengthen the knowledge related to the Strategic Plan, later based on the information obtained in the research techniques such as the interview made to the Manager and the surveys carried out to the five (5) employees And 236 frequent customers of the company, data registered in the company until the end of 2016. Among the methods applied in the research are the Statistical Method, Inductive Method and the Deductive Method; Within the techniques applied were conducted the interview and the survey, under these conditions these data collaborated to be able to formulate the strengths and weaknesses, While analyzing the external factors such as economic, political, technological and social factors and the analysis of the five forces of PORTER was determined the opportunities and threats, always relying on field research in the design of the SWOT matrix . The internal and external factors were then evaluated through the application of the EFI and EFE matrices, followed by an analysis of the Mission and Vision, in order to rethink a new Mission and Vision. On the other hand, it was possible to determine that PROMETAL possesses as the greatest strength the Very good quality of the products of the company being the biggest weaknesses that the company does not have advertising, but above all the lack of publicity and promotion that have not allowed this Company could be better developed, from this analysis it was possible to establish that the weighted factor of the EFI matrix, obtained a value of 2.37 which implies that the company is not strong internally, and that it has some weaknesses that can destabilize it and In the Matrix EFE a value of 2.54 that determines that the Opportunities are above of Threats. With these considerations through the Matrix of High Impact, four strategic objectives were proposed, among which it is determined Promote in the human talent of the company a culture of personalized attention to the client with a budget for its fulfillment of $ 1,080.00 dollars, Through Technological systems improve the relationship with suppliers of materials with a budget for compliance of $ 850.00 dollars; Increase sales through an advertising plan, in the mainstream media in the city of Loja with a budget for compliance of $ 820.00 dollars; And, Encouraging a better performance of human talent through training courses for the company staff, in order to satisfy customers with a budget for compliance of $ 840.00 dollars, all these goals with a budget Of $ 850.00 dollars that will be covered by the partners of the company PROMETAL, finally it has come to determine the conclusions and recommendations based on the market study and the proposal the recommendations that should be made in front of the implementation of the Plan Strategic. Finally, the respective conclusions are presented and with each of them the necessary recommendations are made for the work.